Sensor-Based Waste Level Monitoring and Alerting Mechanism - Srinivasan J (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Rapid population increase and ineffective disposal techniques are making waste management more complex in both urban and rural locations. Traditional garbage collection methods frequently result in overflowing bins, unhygienic conditions, and wasteful resource allocation since they rely on preset timetables rather than actual bin fill levels. To solve these problems, our study presents an autonomous waste management up-cycling device to improve waste disposal efficiency and an innovative bin system based on the Internet of Things (IoT) that continuously records tracks, and reports garbage levels in real-time. An LCD screen, a GPS module, an ultrasonic sensor, and an ESP8266 microprocessor make up this system. The GPS module tracks the location, and the ultrasonic sensor measures the quantity of waste in the trash can. To ensure prompt collection, an automated SMS notice is issued to garbage collectors and municipal authorities once the container is filled. Furthermore, a web-based interface updates the bin’s state, enabling remote monitoring. An LCD allows on-site employees to monitor trash levels as well, increasing operational effectiveness. This system uses IoT.Technology to optimize garbage collection, limit overflow, and lower labor and fuel expenses by only sending out collection vehicles when needed. By encouraging appropriate recycling, automated waste segmentation improves sustainability. This intelligent waste management system ensures cleaner surroundings and better public hygiene by coordinating with eco-friendly trash disposal methods and innovative city projects.